Acute respiratory distress syndrome in traumatic brain injury: how do we manage it? - Torre, Valentina Della; Badenes, Rafael; Corradi, Francesco; Racca, Fabrizio; Lavinio, Andrea; Matta, Basil; Bilotta, Federico; Robba, Chiara (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Abstract: Traumatic brain injury (TBI) is an important cause of morbidity and mortality worldwide. TBI patients frequently suffer from lung complications and acute respiratory distress syndrome (ARDS), which is associated with poor clinical outcomes. Moreover, the association between TBI and ARDS in trauma patients is well recognized. Mechanical ventilation of patients with a concomitance of acute brain injury and lung injury can present significant challenges. Frequently, guidelines recommending management strategies for patients with traumatic brain injuries come into conflict with what is now considered best ventilator practice. In this review, we will explore the strategies of the best practice in the ventilatory management of patients with ARDS and TBI, concentrating on those areas in which a conflict exists. We will discuss the use of ventilator strategies such as protective ventilation, high positive end expiratory pressure (PEEP), prone position, recruitment manouvers (RMs), as well as techniques which at present are used for ‘rescue’ in ARDS (including extracorporeal membrane oxygenation) in patients with TBI. Furthermore, general principles of fluid, haemodynamic and hemoglobin management will be discussed. Currently, there are inadequate data addressing the safety or efficacy of ventilator startegies used in ARDS in adult patients with TBI. At present, choice of ventilator rescue strategies is best decided on a case-by-case basis in conjunction with local expertise.